Smart Student Character: Edukasi Bijak Penggunaan Gadget, Kontrol Diri, dan Disiplin Sekolah pada Siswa SMA - Ogy Yan Hesta; Rahmadhania Rizanty; Dwi Prasetyo Rini; Jean Rala Bangkit; Marsa Triana Ayu (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
Poorly managed gadget use may disrupt students’ concentration, sleep patterns, academic responsibilities, and compliance with school rules. This community service program aimed to improve students’ understanding, awareness, and commitment to wise gadget use, strengthen self-control, and promote school discipline. The program was conducted on June 11, 2026, at SMA Pelita Tiga No. 3 Jakarta and involved 150 students from grades X and XI. An educational-participatory approach was implemented through interactive lectures, peer-to-peer learning, a “The Power of Habit” workshop, discussion, and reflection. The materials addressed the functions and risks of gadgets, triggers of automatic use, strategies for managing time and notifications, and the relationship between digital habits and discipline. Evaluation used participation observations, reflective discussion, and a partner satisfaction instrument. The results showed that students could distinguish productive from unproductive gadget use, identify triggers of excessive use, and formulate practical actions such as establishing gadget-free periods, reducing notifications, and prioritizing academic tasks. Partner satisfaction reached 42 out of 50, with a mean score of 4.2 or 84 percent, indicating that the program was rated good. The program is relevant for strengthening school counseling services and peer-based initiatives. However, long-term behavioral change cannot yet be concluded because pretest-posttest measurement and follow-up mentoring were not completed.